Respuesta :

Move all the exponentials to one side, and all the constants to the other:

[tex] \dfrac{c^t}{b^t} = \dfrac{v}{p} [/tex]

You can rewrite the left hand side as

[tex] \left(\dfrac{c}{b}\right)^t = \dfrac{v}{p} [/tex]

Consider the logarithm base [tex] \frac{c}{b} [/tex] of both sides:

[tex] log_{\frac{c}{b}}\left(\dfrac{c}{b}\right)^t = log_{\frac{c}{b}}\left(\dfrac{v}{p} \right) [/tex]

Logarithm and exponential simplifies:

[tex] t = log_{\frac{c}{b}}\left(\dfrac{v}{p} \right) [/tex]

ACCESS MORE